Taking the Leap Toward Publication - Candace Schlein; Maryam Wagner (Canadian Society for Studies in Education, 2012)
In this article we reflect on some of our interactions with graduate and new scholar authors via our work as long-standing members of the current and former Editorial Board of the Canadian Journal for New Scholars in Education/ Revue canadienne des jeunes chercheures et chercheurs en éducation (CJNSE/RCJCÉ). Using our reflected experiences as a foundation, we discuss here some of the details involved in publishing a first article. The overall aim of this article is to demystify the publishing process and to inform graduate students about the required elements and processes involved in the preparation of their manuscripts and the subsequent process of publication from submission, to reviews, and editing. In turn, we hope to encourage new researchers and theorists to take the leap and publish their first articles.